Kajian Tingkat Degradasi Pada Pelaksanaan Konstruksi Jalan Beraspal - Ranindita, Atri; Putra, Sasana; Diana, I Wayan (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
One causes of construction failure on flexible pavement is changed composition of the aggregate gradation in asphalt mixture of the plan due to mechanical or non-mechanical process. Aggregates can occur degradation, ie gradation changes due to aggregate breakage of grains. Aggregate degradation can be caused by both mechanical and chemical processes. The decrease in quality occurring in the asphalt mixture is thought to be due to the aggregate gradation change in the asphalt mixture. To find this out, a study on the degradation level of flexible pavement construction is conducted,from Asphalt Mixing Plant to overlay location. Used mixture are Asphalt Concrete-Wearing Course produced by PT. Manggung Polah Raya for location on Sultan Agung Street, Bandar Lampung, Lampung and PT. Rindang Tigasatu Pratama for location on Teuku Cik Ditiro Street, Bandar Lampung, Lampung. Test of samples performed are extraction test and sieves analysis test. From the research result, it is founded that there is degradation during transport of asphalt mixture from Asphalt Mixing Plant to the location. Average degradation percent of location I, location II and location III PT. Manggung Polah Raya and PT. Rindang Tigasatu Pratama is %CA decreased by 5.17%, %FA increased by 3.67% and %filler increased 1.50%. Factors affecting degradation are due to work execution, specific gravity of aggregate and time of transport.Keywords: Road Pavement, Asphalt Concrete, Degradation